Eradication Technique of Prosopis juliflora for Pilot Study in Uttar Pradesh - Kumar, Dinesh; Srivastava, Sanjay Kumar; Kumar, Mukesh; Kairon, Vinod Kumar; Kunwar, Vishal; Singh, Shubham; Kumar, Amit (Indian Forester, 2025)
A safe and effective method is lacking for ecorestoration of forest area affected by Prosopis juliflora. Studies were conducted on root suckering and coppicing behaviour of this species. Lateral roots of the standing plants of P. juliflora were not found to have a natural tendency to produce root suckers. Young plants (<20 cm height) were found to be growing randomly at 0.3 to 6.1 plants/m2 plant density on the forest floor; these plants were of seed origin and were not connected with the roots of existing plants. Coppice shoots of P. juliflora arose from the junction between stem and root or slightly above this region. To undertake pilot trial, it was suggested that P. juliflora plants be removed by severing the tap root about 50 cm below the ground level and cutting off the lateral roots close to the plant without digging out the lateral roots. In order to physically suppress and outgrow the new P. juliflora, it was suggested to place, in the beginning of monsoon season, 1-2 tufts of Saccharum spontaneum, S. bengalense, Chrysopogon fulvus, Eulaliopsis binata or other hardy local grasses along with soil over the pit created by removal of P. juliflora. A mixture of native tree or shrub species should be planted at a density of 2,500 plants/ha to establish tree cover in the area to create a permanent tree canopy.